2023
DOI: 10.1097/js9.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes following intracorporeal versus extracorporeal anastomosis after laparoscopic right and left-sided colectomy: a propensity score-matched study

Abstract: Background: To compare the short-term outcomes of patients undergoing intracorporeal anastomosis (IA) during laparoscopic colectomy to those undergoing extracorporeal anastomosis (EA). Methods and materials: The study was a single-centre retrospective propensity score-matched analysis conducted. Consecutive patients who underwent elective laparoscopic colectomy without the double stapling technique between January 2018 and June 2021 were investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Previous studies have not reported a reduction in operative time. Some reports indicate that IA and EA are comparable in terms of operative time[ 13 ], but in most reports, IA is longer than EA[ 14 , 15 ], and this applies to robotic surgery[ 16 , 17 ]. On the other hand, the amount of bleeding was significantly lower in IA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not reported a reduction in operative time. Some reports indicate that IA and EA are comparable in terms of operative time[ 13 ], but in most reports, IA is longer than EA[ 14 , 15 ], and this applies to robotic surgery[ 16 , 17 ]. On the other hand, the amount of bleeding was significantly lower in IA.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of our study include being a retrospective single-centre, non-randomized study and during a period in which there were other intervening factors such as the use of three rows of staples and intelligent sealing. Almost all anastomoses were extracorporeal, which did not allow for further analysis of predictors of complications based on the type and method of anastomosis as intracorporeal anastomosis was found to be associated with lower rates of complications [20][21][22]. The numbers included are relatively small yet were sufficient to obtain significant results in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to operating time: IA is associated with a longer surgical time in most comparative studies, though the difference is not always signi cant. [32] Comparing laparoscopic and robotic approaches, recent studies show the robotic approach entails extended surgery time and higher costs [20][21][22]. However, systematic reviews and meta-analyses reveal lower rates of overall morbidity, anastomotic dehiscence, and SSIs (super cial and deep) in robotic surgery [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of comparisons with the laparoscopic approach, there are few but promising ndings for R-TIA. [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%